Urban freight policy maturity and sustainable logistics: Are they related? - Jonathan Cowie; Keith Fisken (Journal of Shipping and Trade (JST), 2023)
Problems associated with urban freight are well known and documented in the academic literature, particularly with regards to the impact on air quality and general intrusion of public space. As a defining principle however, urban freight has generally been left solely to operate on free market principles, with policy interventions generally being solely 'problem' focused. Given the underlying economics of freight transport, and particularly the cost advantages of road-based transport, intervention by public bodies is clearly a critical issue, however to date has received limited attention in the urban freight research literature. The aim of the current research is to examine if there is any relationship between the extent of local authorities' freight policy development and the success of a policy driven (green) urban freight pilot initiative. This is based on five city case studies located across Northern Europe and uses an adapted form of Kiba-Janiak (Res Transp Bus Manag 24:4-16, 2017, https://doi.org/10.1016/j.rtbm.2017.05.003) five stages of 'city maturity' with regards to urban freight policy development. Each city's policy framework is mapped onto one of these states of maturity. The success of the pilots in each city is then matched against the maturity of the policy framework. Taken at face value, the results show little correlation between the two, and hence the success of any initiative would appear to be independent of the policy framework. The real issue however is found to be low urban freight transport policy maturities within the case study sample, specifically a lack of tactical and operational functions, i.e. the ability to actually do something. The concern at the more general level is that what this leads to is policy stagnation.
Keywords: 650; City logistics; Cycle logistics; Last mile logistics; UFT policy maturity; Urban consolidation centre